Familial genetic cancer risk assessment in a male patient with pancreatic and breast cancer with a silent BRCA2 mutation - Bapat, Ashwini; Gahlaut, Siddharth; Noor, Aijaz Ul; John, Jisha; Busheri, Laleh; Reddy, Ruhi; Shaikh, Shahin; Nare, Smeeta; Mannan, Ashraf ul; Dixit, Santosh; Mishra, Rupa; Koppiker, CB (Indian Journal of Case Reports, 2024)
Male breast cancer (MBC) is relatively rare, accounting for A, pE2918E) in the proband. Cascade testing of 34 family members identified 5 of the family members as carriers of this BRCA2 variant. Among them, two members were breast cancer affected and three were unaffected healthy carriers. Our study demonstrates the clinical relevance of this silent BRCA2 mutation and emphasizes the need for further experimental studies to elucidate its functional role in breast cancer pathology.